Distinct healing pattern of maxillary sinus augmentation using the vitroceramic Biosilicate®: Study in rabbits - Thompson, Francis Cazzeli; Matsumoto, Mariza Akemi [UNESP]; Biguetti, Claudia Cristina; Rennó, Ana Claudia Muniz; de Andrade Holgado, Leandro; Santiago Junior, Joel Ferreira; Munerato, Marcelo Salles; Saraiva, Patrícia Pinto (Elsevier, 2019)
Objectives: To follow healing process of augmented maxillary sinus in rabbits analyzing the histological pattern of bone tissue formation, along with the osteogenic activity and vascularization using a bioactive vitroceramic in comparison to deproteinized bovine bone associated or not with autogenous bone graft. Design: Forty five male adult New Zealand rabbits, 5 months of age, mean weight of 4 Kg, underwent bilateral sinus augmentation surgeries to be divided in five groups: G – (Control) particulate autogenous bone graft (AG), BO - deproteinized bovine bone, BO+G - deproteinized bovine bone + AG, BSi –vitroceramic, and BSi + G – vitroceramic +AG. After 15, 45 and 90 days, all animals were euthanized for specimen's removal to be analyzed under light microscopy, histomorphometry, and immunohistochemistry for Runx2 and VEGF labeling. Results: G, BO and BO+G groups healed uneventfully, allowing the formation of mature remodeling bone at day 90, regarding the association of AG with the biomaterial. On the other hand, BSi and BSi + G groups showed an important cellular reaction and granulation/fibrous tissue formation from the first to the last period of observation. Runx-2 and VEGF immunolabeling were coherent with this result. However, histomorphometry did not reveal significant differences considering new bone formation. Conclusions: Reconstructed maxillary sinuses using Biosilicate® permitted satisfactory new bone formation in comparison to the deproteinized bovine bone and AG. However, the presence of granulation/fibrous tissue and inflammatory cells associated to the degrading biomaterial indicate that further studies should be careful performed considering the immunological aspect of this new biomaterial.
Keywords: Animal model; Biomaterials; Sinus floor elevation; Vitroceramic; Wound healing